Integrating Sustainability and Islamic Philanthropy: A Financial Framework for Cash Waqf Participation - Abbas, Nasir; Shahid, Muhammad Sadiq; Naheed, Khawar (Audit and Accounting Review, 2026)
This conceptual study aims to develop an integrated framework for cash waqf participation by combining the Theory of Planned Behavior (TPB) with Islamic behavioral constructs, institutional dimensions, and digital transformation perspectives in the context of sustainable development. Based on a systematic review of recent research on cash waqf and Islamic social finance, the study synthesizes fragmented findings into a unified model that links individual donor behavior, waqf institutional mechanisms, and Sustainable Development Goals (SDGs). The framework highlights institutional governance, digital platforms, and perceived developmental impact as critical channels through which donors’ attitudes, perceived behavioral control, subjective norms, perceptions of Shariah compliance, moral obligation, and religiosity shape cash waqf participation. The current study offers practical guidance for waqf institutions and policymakers aiming to strengthen fundraising effectiveness and impact reporting. Furthermore, it provides a theoretical foundation for future empirical research and policy design in the field of Islamic social finance. This study suggests ways in which these goals can be achieved through the sustainable use of the waqf mechanism to achieve SDGs. This is the first study to develop a conceptual framework for cash waqf. Additionally, this study provides a theoretical basis for future research to advance Islamic social finance and waqf paradigms in the digital economies.